THE USE OF CLASSROOM BLOG IN TEACHING WRITING TO JUNIOR HIGH SCHOOL STUDENTS : A Case Study Of Second Year Junior High School In One Of Public Schoool In Bandung Year 2011/2012 - Artvianti, Eugenia Ines Dwi (2013)
ABSTRACT This research investigated the implementation of classroom blog in teaching writing on the second grader in one of public school in Bandung. It was also aimed to find out the strength and challenges faced by the students in using Classroom Blog as a learning tool to write. A case-study design was used in this study and the data collected through observation, interview and document analysis. Then, the data that had been gathered were analyzed qualitatively. The results were in line with previous research which stated that classroom blog helps activate interaction with readers, create an audience and feedback for their writing, this findings are compatible with prior research findings from (Song & Chan, 2008; Zhang, 2009; Galien; 2010).The research also found out that Classroom Blog has its strength and challenges. Classroom Blog enables the students to: (1) have a fun learning environment; (2) write easily; (3) get feedbacks from teacher and peers; (4) discuss more with friends and teacher outside classroom easily; (5) access more reference for students' writing; (6) get more motivation to write; (7) have their personal space to read and write in a community; and (8) build their analytical and critical thinking skill. There are also some challenges faced by the students, as follows: (1) technical problems; (2) time management; (3) students' inability to point out mistakes done by their peers; and (4) plagiarism. Overall, the use of Classroom Blog created positive effects to the students writing fluency. For that reason, Classroom Blog is recommended to be used as writing media for students.